Pengaruh pendapatan asli daerah, dana alokasi umum, dan dana alokasi khusus terhadap pertumbuhan ekonomi Kabupaten/Kota Provinsi Jambi - Anjelina, Pebby; Zamzami; Nurhayani, Nurhayani (e-Journal Perdagangan Industri dan Moneter, 2019)
This study aims, (1) To analyze the development of regional original income, general allocation funds, special allocation funds, and economic growth of Jambi Province Regency/City (2) To determine the effect of regional original income, general allocation funds, and special allocation funds on the economic growth of the Regency / City of Jambi Province partially and simultaneously. Data sourced from the Central Statistics Agency of Jambi Province and the Directorate General of Fiscal Balance with panel data analysis method and using descriptive analysis tools. Based on the results of data processing, the following results are obtained: first, the average development of regional original income variables, general allocation funds, special allocation funds, and economic growth fluctuates from year to year. second, (1) Regional original income and special allocation funds have a negative and significant impact on the economic growth of districts/cities in Jambi Province. (2) The general allocation fund has a negative and insignificant effect on the economic growth of districts/cities in Jambi Province. Keywords: Economic growth, Local revenue, General allocation funds, Special Allocation funds Province.